2016
DOI: 10.1136/bmjopen-2016-011362
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study analysing women's childbirth satisfaction and obstetric outcomes across two different models of maternity care

Abstract: ObjectivesTo describe the differences in obstetrical results and women's childbirth satisfaction across 2 different models of maternity care (biomedical model and humanised birth).Setting2 university hospitals in south-eastern Spain from April to October 2013.DesignA correlational descriptive study.ParticipantsA convenience sample of 406 women participated in the study, 204 of the biomedical model and 202 of the humanised model.ResultsThe differences in obstetrical results were (biomedical model/humanised mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 56 publications
2
25
1
3
Order By: Relevance
“…The study verified how the selected demographic characteristics (age, education, place of residence) and the number and type of childbirth are linked to women's satisfaction with childbirth. Previous research has shown that the number of births is in some cases related to women's satisfaction with the birthing experience and that multiparas are more satisfied (Ferrer, et al, 2016). In our case satisfaction proved not to be the decisive factor as the results of the analysis did not show any connection between the number of births and the level of satisfaction with the childbirth experience.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The study verified how the selected demographic characteristics (age, education, place of residence) and the number and type of childbirth are linked to women's satisfaction with childbirth. Previous research has shown that the number of births is in some cases related to women's satisfaction with the birthing experience and that multiparas are more satisfied (Ferrer, et al, 2016). In our case satisfaction proved not to be the decisive factor as the results of the analysis did not show any connection between the number of births and the level of satisfaction with the childbirth experience.…”
Section: Discussioncontrasting
confidence: 55%
“…V raziskavi smo preverjali, kako so izbrane demografske značilnosti (starost, izobrazba, kraj bivanja) ter število in vrsta poroda povezani z zadovoljstvom žensk s porodno izkušnjo. Predhodne raziskave ugotavljajo, da je število porodov v nekaterih primerih povezano z zadovoljstvom s porodno izkušnjo, zadovoljnejše so mnogorodnice (Ferrer, et al, 2016). V našem primeru se je izkazalo, da za zadovoljstvo to ni bil odločilen dejavnik, saj rezultati analize niso pokazali povezanosti med številom porodov in stopnjo zadovoljstva s porodno izkušnjo.…”
Section: Diskusijaunclassified
“…For healthcare professionals, three consequences were satisfaction of the job, which included all areas of medicalised and nonmedicalised care provided (Conesa Ferrer, Canteras Jordana, Ballesteros Meseguer, Carrillo Garcia, & Martinez Roche, ), an increase in the esteem of their profession and in their practice (Fujita et al, ) and the empowerment of staff that built confidence in changing practice.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative measurement of “humanisation in pregnancy and childbirth” has been assessed in a number of ways including the use of the childbirth companion intervention (Brown, Hofmeyr, Nikodem, Smith, & Garner, ) and the Women's views of birth and labour satisfaction questionnaire (Conesa Ferrer et al, ). Questionnaires used in the research were validated for their reliability using pretesting (Baldisserotto, Filha, & Gama, ; Oliveira Morais, do Nascimento Paz, & de Matos Bezerra, ).…”
Section: Methodsmentioning
confidence: 99%
“…During the discussion of stage two, from full dilatation to the birth of baby, it was identified that negative statements made by two childbirth educators were greater than both information and positive statements combined. Studies have identified that the use of positive and negative suggestions may have implications for birth expectations and experiences of women and their birth partner 20 . Suggestions are a communication technique that can lead to subconscious non-volitional changes in perception, mood, and behaviour 21 .…”
Section: Figure 4 Statements Made By Childbirth Educators When Discumentioning
confidence: 99%